Hepatitis C antibody prevalence and behavioral correlates in people who inject drugs attending harm reduction services in Lisbon, Portugal - Curado, Adriana; Nogueira, Paulo Jorge; Virgolino, Ana; Santa Maria, João; Mendão, Luís; Furtado, Cristina; Antunes, Francisco (Frontiers in Public Health, 2022)
The hepatitis C virus (HCV) infection is an important public health problem, affecting millions of people worldwide. People who inject drugs (PWID) are at increased risk of HCV infection due to, among other factors, widespread unsafe injecting practices, such as sharing of infected equipment or unprotected sexual practices. In Portugal, there is a lack of data regarding the proportion of infected persons through injecting drug use. This study aimed to evaluate the anti-HCV prevalence and behavioural correlates of infection in PWID attending harm reduction services in the Metropolitan Area of Lisbon, Portugal. A cross-sectional study with a purposive sample of PWID was undertaken between March 2018 and March 2020. Participants were recruited through harm-reduction services of a non-governmental organization. A rapid diagnostic test for anti-HCV screening was done. Data on drug consumption history and current practices, past HCV testing, care and treatment history, and knowledge regarding hepatitis C were also collected through a questionnaire applied by trained inquirers. A total of 176 PWID participated in the study. An overall prevalence of 70.5% of anti-HCV positive in this population was found. Those with an anti-HCV positive testing result tended to start consuming at a younger age and have a higher consumption of benzodiazepines in the last 30 days. Sharing of needles and other injecting material is a frequent risk behaviour among this group. Also, they are more likely to have attended to an opioid agonist treatment, to have undertaken previous hepatitis C and HIV tests in the past. This study represents an important effort to better understand the HCV prevalence and behavioural correlates of infection among PWID in Portugal, as well as to a better estimate those in need of HCV treatment.